Three-Dimensional Soliton Propagation in Ruby for High-Stability Optical Communication - Firdaus, Rohim Aminullah; Yantidewi, Meta; Khoiro, Muhimmatul; Winarno, Nanang; Ramadani, Riski; Nikmah, Afiyah; Alhusni, Hanan Zaki (POSITRON, 2026)
Optical communication in digitalisation is a significant catalyst in supporting high-speed and large capacity data transmission. However, optical communication applications face substantial challenges, such as energy loss, dispersion effects, and signal stability over long transmission distances. One material that has the potential to overcome these problems is ruby due to its nonlinear characteristics. This research work numerically investigates soliton propagation in ruby material analysis as a Nonlinear Schrödinger Equation numerical modelling and three-dimensional visualisation with Cubic B-Spline, modified Korteweg-de Vries-Zakharov-Kuznetsov, and Boussinesq methods to understand ruby material characteristics more deeply. The simulations show that the soliton waveform remains stable during propagation, with its amplitude confined within approximately -1.05 to 0.35, indicating robust shape preservation under anisotropy and temperature variations. like most previous studies that are limited to one or two dimensional modelling or to dispersive fibre media, this study implement a full 3D NLSE framework tailored to the physical properties of ruby. The results show that both numerical modelling and three-dimensional visualisation indicate that ruby material can maintain the soliton waveform during propagation. This finding suggests that ruby has the potential to be applied in optical communication systems with high stability to support long-distance data transmission.